1984
DOI: 10.1111/j.1467-7717.1984.tb00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Public health aspects of volcanic hazards; Evaluation and prevention of excessive morbidity and mortality due to natural disasters

Abstract: This is a summary of the proceedings of sessions on Volcanic Hazards at the First International Symposium on Public Health in Asia and the Pacific Basin, held 3-11th March 1983, in Honolulu, Hawaii. The Symposium was sponsored by the Association of Schools of Public Health, the U.S. Public Health Service and the Centers for Disease Control (CDC), the World Health Organization (WHO), the South Pacific Commission, and the East-West Center of the University of Hawaii. The full proceedings are being prepared for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(11 reference statements)
0
1
0
2
Order By: Relevance
“…In addition to the direct health impacts resulting in mortality and morbidity, 1 2 3 they also have indirect health impacts due to deterioration of health resources and social capital, leading to ill health 2 and increased health inequality. 4 5 According to the Centre for Research on the Epidemiology of Disasters (CRED), more than 216 million people worldwide were affected by natural disasters each year between 2003 and 2012. The United Nations Office for Disaster Risk Reduction (UNISDR) reported that the overall disaster-related economic losses were estimated between 250 billion and 300 billion USD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the direct health impacts resulting in mortality and morbidity, 1 2 3 they also have indirect health impacts due to deterioration of health resources and social capital, leading to ill health 2 and increased health inequality. 4 5 According to the Centre for Research on the Epidemiology of Disasters (CRED), more than 216 million people worldwide were affected by natural disasters each year between 2003 and 2012. The United Nations Office for Disaster Risk Reduction (UNISDR) reported that the overall disaster-related economic losses were estimated between 250 billion and 300 billion USD.…”
Section: Introductionmentioning
confidence: 99%
“…Klima je tako|er pod utjecajem vulkanskih aktivnosti (12,13 (15). Nakon vulkanske erupcije mogu se razviti akutni i/ili kroni~ni simptomi i bolesti, a utvr|en je odnos "doza-odgovor", pri ~emu se u~inci mogu kretati sve do smrtnog ishoda, posebno pri o{te}enju di{nog sustava.…”
Section: Promjena Klimeunclassified
“…Osobe koje `ive i rade u podru~ju vulkanskih erupcija imaju brojne zdravstvene te{ko}e kao posljedice negativnih u~inka (5,15). Posebnom riziku izlo`eni su radnici koji rade u geotermalnim elektranama, geolozi i osobe uklju~ene u vulkanski turizam ili snimanja dokumentarnih filmova.…”
Section: Specifi~ni U~inci U Uvjetima Profesionalne I/ili Neprofesionunclassified